2014
DOI: 10.3390/ijerph110808542
|View full text |Cite
|
Sign up to set email alerts
|

Human Leptospirosis Trends: Northeast Thailand, 2001–2012

Abstract: The objective of this study was to determine the changing trend of leptospirosis over time in Thailand using two prospective hospital-based studies conducted amongst adult patients with acute undifferentiated fever (AUFI) admitted to Maharat Nakhon Ratchasima Hospital, Nakhon Ratchasima Province, Thailand between July 2001 to December 2002 and between July 2011 to December 2012. During the first period, leptospirosis (98 patients, 40%) and scrub typhus (59 patients, 24.1%) were the two major causes of AUFI. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 13 publications
2
27
0
4
Order By: Relevance
“…Este estudio incluyó 119 pacientes hospitalizados con diagnóstico de leptospirosis, en quienes se encontró una mayor frecuencia de complicaciones, especialmente falla hepática y síndrome de Weil, y una mortalidad general similar a la reportada en Colombia, pero inferior a la informada en algunas series de casos en otros países (22)(23)(24)(25)(26)(27)(28)(29). Se encontró, además, que cerca del 10 % de los pacientes no recibió tratamiento antibiótico a pesar de encontrarse hospitalizado.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Este estudio incluyó 119 pacientes hospitalizados con diagnóstico de leptospirosis, en quienes se encontró una mayor frecuencia de complicaciones, especialmente falla hepática y síndrome de Weil, y una mortalidad general similar a la reportada en Colombia, pero inferior a la informada en algunas series de casos en otros países (22)(23)(24)(25)(26)(27)(28)(29). Se encontró, además, que cerca del 10 % de los pacientes no recibió tratamiento antibiótico a pesar de encontrarse hospitalizado.…”
Section: Discussionunclassified
“…Aunque la frecuencia de complicaciones fue superior a la descrita en la mayoría de las series, la mortalidad no excedió la informada en otros estudios colombianos y en el Sistema Nacional de Vigilancia en Salud Pública (1,5 a 5 %) (6,15,18,22,24,31), y fue inferior a la reportada en las series de casos en otros países (7 a 22 %) (23)(24)(25)(26)(27)(28)(29)32,33). Esta disociación entre una mayor frecuencia de complicaciones y una menor mortalidad es difícil de explicar, especialmente si se tiene en cuenta el gran número de pacientes que presentó síndrome de Weil, complicación asociada con una mayor mortalidad (32)(33)(34).…”
Section: Discussionunclassified
“…The patients who provided 19 of the samples were subsequently shown to have dengue fever by serologic and/or NS1 screening [12]. Only 5 of these patients were amongst the PCR positive samples, showing a relatively low sensitivity for virus detection by RT-PCR in serum samples.…”
Section: Discussionmentioning
confidence: 99%
“…A confirmed diagnosis was subsequently available for 38 of the patients whose samples were included in this study, of which 19 were confirmed as dengue fever, 9 as scrub typhus and 10 as leptospirosis [12]. Dengue serology (IgG and IgM) and NS1 ELISA were undertaken in house at Siriraj hospital, Bangkok, Thailand according to established protocols [13,14].…”
Section: Serum Samplesmentioning
confidence: 99%
See 1 more Smart Citation